2074. Performance and Impact Evaluation of Direct Rapid Antibiotic Susceptibility Testing on Antibiotic Treatment Accuracy in Clinical Setting. (26th November 2018) - Kim, Jeong-Han; Kim, Taek Soo; Song, Sang Hoon; Choi, Jungil; Han, Sangkwon; Kim, Dong Young; Kwon, Sunghoon; Kang, Chang Kyung; Song, Kyoung-Ho; Choe, Pyeong Gyun; Bang, Ji Hwan; Kim, Eu Suk; et al.
Abstract: Background: Timely and effective antibiotics treatment is crucial in early period of bacteremia. Antibiotic susceptibility testing (AST) is essential for choosing an optimal antibiotics treatment, but conventional AST requires 2 days from confirmation of blood culture positivity. Direct rapid antibiotic susceptibility testing (dRAST) based on microfluidic agarose cannel chip technology determines antibiotic susceptibility by time lapse imaging in 6 hours. We evaluated the performance of dRAST to improve selection of adequate antibiotic in clinical practice settings. Methods: Two hundred eighty-three patients with positive blood culture (BC) bottles were included for analysis. BC bottles from these patients were processed by current microbiology analyzer: Microscan for Gram positive strains and VITEK2 for Gram-negative strains. At the same time, AST was performed using dRAST. The susceptibility results were reported to infectious diseases specialists who determine optimal antibiotics based on AST results. We compared the time differences and accuracy of dRAST with those of conventional method. Results: Of 283 patients, 117 (41.5%) patients were infected with Gram positive bacteria, 163 (57.4%) patients were infected with Gram negative bacteria and 3 (1.1%) patients were infected with Gram-positive and -negative bacteria. The total turnaround time for conventional method and dRAST from blood culture collection was 78.3 ± 27.0 and 55.9 ± 18.9 hours, respectively. Seventy-seven of 95 (81.1%) patients who received ineffective or suboptimal antibiotic treatment after confirming the results of Gram stain and 81 of 86 (94.2%) patients who received unnecessary broad-spectrum antibiotic treatment could have received adjusted optimal treatment based on dRAST. Conclusion: The use of dRAST system would accelerate earlier effective antibiotic administration and reduce the antibiotic selective pressure in patients with bacteremia. Disclosures: J. Choi, QuantaMatrix Inc.: Employee, equity interest. S. Han, QuantaMatrix Inc.: Employee, equity interest. D. Y. Kim, QuantaMatrix Inc.: Board Member, equity interest. S. Kwon, QuantaMatrix Inc.: Board Member, equity interest.